Kajian Hukum Tentang Penerapan Fungsi Sosial Pada Hak Cipta - Rahayu, Kanti (Diktum: Jurnal Ilmu Hukum, 2021)
The principle promoted by copyleft is to eliminate economic rights but still carry moral rights in Intellectual Property Rights (IPR). Because some people's assumptions about monopoly and capitalism that appear in IPR are due to the existence of economic rights which then seem to eliminate their social functions. Law Number 19 of 2002 concerning Copyright explicitly explains social functions, but even then it is still limited to education, research, and for law enforcement. If it doesn't fall into that category, then paying royalties is a must. Therefore, with the copyleft system, it must be utilized as much as possible, because basically this copyleft does not violate the concept of copyright. This is because in one copyrighted work that has been copied, there is already a copyright, but in the copyright, a distribution provision is added, as a legal tool that gives everyone the right to use, modify, and redistribute the copyrighted work or its derivatives.